2015
DOI: 10.5129/001041515814224417
|View full text |Cite
|
Sign up to set email alerts
|

Religion and Public Goods Provision: Experimental and Interview Evidence from Catholicism and Islam in Europe

Abstract: Religions such as Catholicism and Islam are generators of substantial amounts of charitable donations and volunteer work, and they sustain themselves as organizations. How do they produce charitable public goods and their own religious club goods when they are open to extensive free-riding? We argue that mainstream religions facilitate club and public goods provision by using their community structures and their theological belief systems to activate the pro-social, generous tendencies of their members. The st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 101 publications
2
20
0
Order By: Relevance
“…They also consider their possession and wealth in this life as far less significant than the rewards they seek in the afterlife. We, therefore, confirm research findings reported by Kilnic & Warner (2015) and Warner et al, (2015). The Quran emphasizes the significance of life after death and, in particular, an individual's soul (or self) being held accountable for its performance during life on Earth.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…They also consider their possession and wealth in this life as far less significant than the rewards they seek in the afterlife. We, therefore, confirm research findings reported by Kilnic & Warner (2015) and Warner et al, (2015). The Quran emphasizes the significance of life after death and, in particular, an individual's soul (or self) being held accountable for its performance during life on Earth.…”
Section: Discussionsupporting
confidence: 91%
“…Accordingly, Catholics consider helping others as part of a choice to live as God tells them to live: that is, following Jesus's example. On the contrary, Muslims believe that what they own in this world is temporary, that all resources are given by God to test believers and that they discharge a huge responsibility by transferring God's property to those in need (Warner et al, 2015).…”
Section: Islam and Donation Behaviormentioning
confidence: 99%
“…Research comparing motives for charity among Muslims and Catholics in several countries suggests that this preference, insofar as it exists, competes with various other motives. Warner et al (2015) show that the notion of "duty to God" triggers thoughts of charity among Muslims but not among Catholics. If God monitors everything, charity performed to please God need not be publicized; in fact, publicizing the act could be viewed as sullying the underlying motives.…”
Section: Islamic Charitiesmentioning
confidence: 88%
“…Finally, consistent with Warner et al . () and Baele et al . (), customers adhering to Muslim and Hindu religions are willing to use trade credit .…”
Section: Sensitivity Tests and Resultsmentioning
confidence: 85%